An overview of ethylene insensitive tomato mutants: Advantages and disadvantages for postharvest fruit shelf-life and future perspective - Mubarok, Syariful; Qonit, Muhammad Abdilah Hasan; Rahmat, Bayu Pradana Nur; Budiarto, Rahmat; Suminar, Erni; Nuraini, Anne (Frontiers in Plant Science, 2023)
The presence of ethylene during postharvest handling of tomatoes can be the main problem in maintaining fruit shelf-life by accelerating the ripening process and causing several quality changes in fruit. Several researchers have studied the methods for improving the postharvest life of tomato fruit by controlling ethylene response, such as by mutation. New ethylene receptor mutants have been identified, namely Sletr1-1, Sletr1-2, Nr (Never ripe), Sletr4-1, and Sletr5-1. This review identifies the favorable and undesirable effects of several ethylene receptor mutants. Also, the impact of those mutations on the metabolite alteration of tomatoes and the future perspectives of those ethylene receptor mutants. The review data is taken from the primary data of our experiment related to ethylene receptor mutants and the secondary data from numerous publications in Google Scholar and other sources pertaining to ethylene physiology. This review concluded that mutation in the SlETR1 gene was more effective than mutation in NR, SLETR4, and SLETR5 genes in generating a new ethylene mutant. Sletr1-2 mutant is a potential ethylene receptor mutant for developing new tomato cultivars with prolonged fruit-shelf life without any undesirable effect. Therefore, that has many challenges to using the Sletr1-2 mutant for future purposes in breeding programs.